2024
DOI: 10.1021/acs.inorgchem.3c04404
|View full text |Cite
|
Sign up to set email alerts
|

Two Short-Wave UV Antimony(III) Sulfates Exhibiting Large Birefringence

Yang Lan,
Han Luo,
Luli Wang
et al.

Abstract: In the present work, we have successfully obtained two new UV antimonybased sulfates, NH 4 Sb(SO 4 ) 2 and Ca 2 Sb 2 O(SO 4 ) 4 , by a conventional hydrothermal method. Interestingly, both compounds share similar structural building blocks, such as SbO 4 seesaws and SO 4 tetrahedra, yet they endow discrepant birefringence values measured at 546 nm with values of 0.150 and 0.114, respectively, owing to the different distortions of the SbO 4 groups with SCALP electrons. Moreover, both compounds display large ban… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 62 publications
0
1
0
Order By: Relevance
“…Studies have demonstrated that the macroscopic optical properties of materials are determined by their functional groups, underscoring the significance of selecting the appropriate functional group. In recent years, non-π-conjugated tetrahedral anionic groups (e.g., SO 4 , PO 4 , and SeO 4 ) have garnered significant attention due to their wide optical transmission window. This feature is particularly advantageous for the development of optical crystals suitable for short-wave UV applications, as exemplified by the compounds Li 2.9 Cs 1.1 (SO 4 ) 2 (exp. 5.39 eV), GdSr 3 (PO 4 ) 3 (exp.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have demonstrated that the macroscopic optical properties of materials are determined by their functional groups, underscoring the significance of selecting the appropriate functional group. In recent years, non-π-conjugated tetrahedral anionic groups (e.g., SO 4 , PO 4 , and SeO 4 ) have garnered significant attention due to their wide optical transmission window. This feature is particularly advantageous for the development of optical crystals suitable for short-wave UV applications, as exemplified by the compounds Li 2.9 Cs 1.1 (SO 4 ) 2 (exp. 5.39 eV), GdSr 3 (PO 4 ) 3 (exp.…”
Section: Introductionmentioning
confidence: 99%